2022
DOI: 10.1089/jop.2021.0123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of an Eyedrop Containing Hyaluronic Acid and Ginkgo Biloba in the Management of Dry Eye Disease Induced by Cataract Surgery

Abstract: Purpose: To evaluate the prevalence of dry eye disease (DED) after cataract surgery, and the impact of hyaluronic acid and ginkgo biloba eyedrops (HA-GB). Methods: Forty patients with no DED received Ocular Surface Disease Index (OSDI) questionnaire, assessment of conjunctival hyperemia and epithelial damage, fluorescein tear break-up time (TBUT) at baseline, day 1, week 1, and 4; adherence and tolerability were checked at weeks 1 and 4. At day 0 patients underwent cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…In a longitudinal approach, our results showed a statistically significant decrease in OSDI scores in the HA-GX group after six weeks of treatment. This trend corresponds to that shown by several studies using the same tear (HA-GX) to assess dry eye symptoms [ 27 , 28 , 43 , 45 ]. Other studies have also shown a decrease in the OSDI score when using tears that combine HA with other molecules [ 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a longitudinal approach, our results showed a statistically significant decrease in OSDI scores in the HA-GX group after six weeks of treatment. This trend corresponds to that shown by several studies using the same tear (HA-GX) to assess dry eye symptoms [ 27 , 28 , 43 , 45 ]. Other studies have also shown a decrease in the OSDI score when using tears that combine HA with other molecules [ 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 86%
“…This trend corresponds to that shown by several studies using the same tear (HA-GX) to assess dry eye symptoms [ 27 , 28 , 43 , 45 ]. Other studies have also shown a decrease in the OSDI score when using tears that combine HA with other molecules [ 43 , 44 , 45 , 46 , 47 , 48 ]. The SPEED score also showed a statistically significant improvement at the end of the study in the HA-GX group.…”
Section: Discussionsupporting
confidence: 86%
“…Artificial tear drops are widely used among both healthy individuals and in DED patients (Table 1). 9–33 New products, in the form of osmoprotectants, lipid-based formulations, hyaluronic acid preparations/combinations, and multicomponent AT preparations, have emerged into the market. Despite a number of new studies comparing different AT formulations, it is hard to make comparisons between preparations because of variable patient populations tested and variable endpoints.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there seems to be no evidence of superiority of a particular AT formulation over another or better efficacy of any multicomponent AT formulation over a basic one-component AT formulation in a particular subset of patients with DED (Table 1). 9–33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation